Teachers' self-efficacy and readiness towards the teaching of higher order thinking skills at pondok pesantren Al-Ihsan Ikadi, Riau, Indonesia - Asrofi (Institute of Education, International Islamic University Malaysia, 2013)
The study investigated the teachers' self-efficacy and readiness towards the teaching of higher order thinking at PondokPesantren Al-Ihsan IKADI Riau, Indonesia. Specifically, it attempted to examine the teachers' level of self-efficacy as well as to gauge their readiness in teaching higher order thinking skills across the curriculum. It also examined the potential factors that may have affectedthe teachers' self-efficacy and readiness as well as to ascertain the relationship between their self-efficacy and readiness in the teaching of higher order thinking skills. The research was conducted using a modification survey adapted from The New Millennium in Mind designed by James Tebbs (2000). The respondents were 66 teachers from PondokPesantren Al-Ihsan IKADI Riau. The findings indicated that majority of the teachers were not highly confident with their ability and ready to teach higher order thinking skills to the students. Their level of self-efficacy and readiness were average. Moreover, this study also suggested that most of the teachers had insufficient knowledge and understanding of higher order thinking skills as well as the strategies to teach these skills due to inadequate trainings. Hence, investments in house seminars, trainings, or workshops on higher order thinking skills were strongly recommended to improve teachers' capability in teaching higher order thinking skills at PondokPesantren.